Development of magnesium-silicate-hydrate (M-S-H) cement with rice husk ash - Sonat, Cem (2020)
Rice husk ash (RHA) is a waste material obtained from the combustion of rice hulls. The properties of RHA, such as its crystallinity and reactivity, depend on the combustion conditions. This study investigated the use of RHA as a silica source in MgOsingle bondSiO2 samples. Two different RHA sources (crystalline and amorphous) were used in comparison to microsilica (MS), which is commonly used in MgOsingle bondSiO2 formulations to form magnesium silica hydrate (M-S-H). Isothermal calorimetry and pH measurements were used to analyze the progress of hydration. In addition to compressive strength measurements, microstructural analysis was performed via XRD, TG/DTG, FTIR and FESEM. Samples containing amorphous RHA as the silica source achieved the highest compressive strengths at early ages (34 MPa at 7 days), whereas those containing MS revealed the highest strengths in the long term (47 MPa at 56 days). This was in line with the faster dissolution rate of amorphous RHA in comparison to MS, as observed in pH measurements. The formation of M-S-H was clearly observed in all samples containing amorphous RHA and/or MS. The use of crystalline RHA led to low strengths, which was provided by brucite in the absence of M-S-H. Combination of amorphous RHA with MgO resulted in M-S-H formation, which was accompanied with a notable mechanical performance. Utilization of amorphous RHA in MgO systems could not only lead to strength gain, but also bring environmental and economic benefits.